Having a single language interest autonomously predicts L2 achievement: Addressing the predictive validity of L2 grit. (August 2022) - Alamer, Abdullah
Abstract: The present study aims to evaluate the role of 'autonomous single language interest' (ASLI) and assess its applicability and predictive validity for subsequent language achievement. ASLI, a refined version of 'consistency of interest' (CI) from grit, postulates that language students who have one autonomous language interest during their study (e.g., during the university setting) would achieve the language more successfully than those who have multiple language-unrelated interests/projects besides their language study. To evaluate this construct, 235 undergraduate English students were tracked over roughly one academic year. The validation of the single language interest (SLI) construct was achieved using exploratory structural equation modeling (ESEM). The analyses indicated a reliable and valid scale of SLI. The predictive moderated model offered unique information about how SLI is related to L2 achievement after one academic year. The effects of SLI on L2 achievement are positive when students have SLI in an autonomous manner; hence the name ASLI, but negative when students' have SLI in a controlled manner (e.g., with internal/external pressure). The effects hold constant while controlling for students' initial language achievement. Conceptual and educational implications are discussed. Highlights: Previous research indicated weak or even negative predictive power of 'consistency of interest' (from grit) for language-related outcomes. The present study offers an alternative construct, autonomous single language interest (ASLI), a refined version of 'consistency of interest' * ASLI decribes L2 students who have one autonomous language interest during their study. The predictive model indicated single language interest (SLI) predict achievement depending on students' motivational profile. The effect of ASLI on achievement is positive when students have their SLI autonomously.